Satisfaction towards clinical learning environment and its associated factors among undergraduate nursing students at public universities in Northwest Ethiopia, 2022. A multi-center cross-sectional study - Alamirew Enyew Belay; Eleni Tesfaye Tegegne; Asemarie Kebede Shitu; Kibret Enyew Belay; Asnake Gashaw Belayneh (Elsevier, 2024)
Background: The clinical learning environment is a multidimensional entity that affects the clinical learning outcomes of nursing students. Most studies in Ethiopia showed that nursing students' clinical competency was below half and their satisfaction with clinical practice is crucial to enhance their competency. However, in Ethiopia satisfaction of nursing students with their clinical learning environment is unknown. Objective: This study aimed to assess satisfaction with the clinical learning environment and associated factors among undergraduate nursing students. Methods: Institution-based cross-sectional study was conducted in public universities, in northwest Ethiopia. A total of 416 undergraduate nursing students were selected by a simple random sampling technique. Data were collected by a structured, pre-tested, self-administered questionnaire, entered into Epi-Info and exported to SPSS for analysis. Bivariable and multivariable binary logistic regression analyses were done to test the association. The odds ratio at 95 % CI and P-value < 0.05 was used to ascertain statistical significance. Results: Of the study participants, one hundred seventy-three (41.6 %) were satisfied with their Clinical learning environment. Third-year students (AOR = 0.41, 95 % CI: 0.22, 0.74), having pre-clinical orientation (AOR = 7.17, 95 % C.I: 3.33, 15.4) comfort on ward rotation (AOR = 2.01, 95 % CI: 1.06, 3.77), less frequent supervision (AOR 0.44, 95 % C.I: 0.24, 0.81), practice at primary hospital (AOR = 3.40, 95 % C.I: 1.20, 9.62), and clinical staff support (AOR = 2.59, 95 % C.I: 1.29, 5.17) were factors significantly associated with their satisfaction. Conclusion: The nursing students' satisfaction with their clinical learning environment was low. Thus, it would be better if nursing students have clinical practice in primary hospitals with pre-clinical orientation, and frequent supervision. In addition, it would be better if hospital staff provided support for nursing students while doing procedures.